2018
DOI: 10.1212/nxi.0000000000000496
|View full text |Cite
|
Sign up to set email alerts
|

The MRI central vein marker; differentiating PPMS from RRMS and ischemic SVD

Abstract: ObjectiveTo determine whether the assessment of brain white matter lesion (WML) central veins differentiate patients with primary progressive MS (PPMS) from relapsing-remitting MS (RRMS) and ischemic small vessel disease (SVD) using 3T MRI.MethodsIn this cross-sectional study, 71 patients with PPMS, RRMS, and SVD were imaged using a T2*-weighted sequence. Two blinded raters identified the total number of WMLs, proportion of WMLs in periventricular, deep white matter (DWM) and juxtacortical regions, and proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
4
9
0
Order By: Relevance
“…We found no significant differences in the presence and proportions of lesions with CVS in relapsing versus progressive MS subtypes, in accord with previous studies. 6,32 These findings are consistent with the CVS reflecting a common lesion pathogenesis among MS subtypes. 32 Of note, PMS subjects trended toward greater proportion of CVS+ lesions versus RRMS subjects.…”
Section: Pms Rrms P = 0077supporting
confidence: 84%
“…We found no significant differences in the presence and proportions of lesions with CVS in relapsing versus progressive MS subtypes, in accord with previous studies. 6,32 These findings are consistent with the CVS reflecting a common lesion pathogenesis among MS subtypes. 32 Of note, PMS subjects trended toward greater proportion of CVS+ lesions versus RRMS subjects.…”
Section: Pms Rrms P = 0077supporting
confidence: 84%
“…Evidence is accumulating rapidly that MS lesions are more often traversed by veins than non-MS white matter hyperintensities, such as those related to migraine or hypertension. 19,6467 Two small studies have suggested the use of a 40% cut-off value to distinguish MS lesions (40% or more lesions are traversed by a central vein) from non-MS lesions. 66,68 This is in keeping with another in vivo study which found that 80%–94% of periventricular MS lesions contain a central vein, which corresponds to >90% sensitivity and specificity.…”
Section: Advanced Sequencesmentioning
confidence: 99%
“…Further correlation with clinical data 55 or biochemical data, such as serum ferritin levels 56 would be straightforward. Note also that 3D gradient echo MRI will likely become part of routine imaging protocols for MS, as it is required for the detection of the central vein sign as a diagnostic marker for MS. [57][58][59][60][61] Lastly, this approach may also be sensitive to diffuse WMwide remyelination rendered possible by future treatment approaches for MS, and may complement measures of remyelination in focal lesions using magnetization transfer imaging, 62 myelin water imaging, 28,63,64 or MR phase based approaches. 65,66 This work has some limitations.…”
Section: Discussionmentioning
confidence: 99%